Advancements in cold spraying for polymer matrix composites: enhanced LSP and EMI shielding performance — review and future directions - Bugra Karahan; Ismail Ozdemir; Thomas Grund; Niclas Hanisch; Thomas Lampke (Journal of Materials Science: Materials in Engineering)
Abstract Polymer matrix composites (PMCs) have emerged as critical materials in lightweight engineering applications due to their excellent mechanical properties and design versatility. However, their inherent limitations in electrical and thermal conductivity necessitate metallization, particularly for applications such as lightning strike protection (LSP) and electromagnetic interference (EMI) shielding. Cold spraying, a low-temperature metallization technique, addresses the shortcomings of conventional methods by enabling the deposition of dense, oxide-free, and highly conductive coatings with minimal damage to the composite substrate. This review provides a comprehensive overview of advancements in metallization techniques, with a focus on cold spraying, to enhance the electrical and thermal performance of PMCs for LSP and EMI shielding. The combination of PMCs with conductive materials presents an innovative approach to achieving lightweight, corrosion-resistant, and efficient LSP and EMI shielding solutions, offering significant advancements in surface functionalization. Future research directions include the exploration of hybrid metallization strategies and the integration of cold spraying with additive manufacturing, highlighting their potential to create multifunctional and high-performance PMC-based systems. Additionally, emerging trends such as novel or smart materials, optimization of cold spray processes through advanced modeling, and the translation of these innovations into industrial applications are discussed.